2009
DOI: 10.3201/eid1502.080637
|View full text |Cite
|
Sign up to set email alerts
|

European Bat Lyssavirus Transmission among Cats, Europe

Abstract: We identifi ed 2 cases of European bat lyssavirus subtype 1 transmission to domestic carnivores (cats) in France. Bat-to-cat transmission is suspected. Low amounts of virus antigen in cat brain made diagnosis diffi cult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 12 publications
0
76
0
3
Order By: Relevance
“…The isolated virus showed a high sequence identity to viruses that were isolated from serotine bats (Eptesicus serotinus) from the same region (Müller et al, 2004). Recently, spillover infections into domestic cats in France in 2006 and 2007 highlighted the veterinary public health importance of bat rabies (Dacheux et al, 2009), even in countries otherwise considered 'free' of classical rabies caused by rabies virus (RABV).…”
Section: Introductionmentioning
confidence: 99%
“…The isolated virus showed a high sequence identity to viruses that were isolated from serotine bats (Eptesicus serotinus) from the same region (Müller et al, 2004). Recently, spillover infections into domestic cats in France in 2006 and 2007 highlighted the veterinary public health importance of bat rabies (Dacheux et al, 2009), even in countries otherwise considered 'free' of classical rabies caused by rabies virus (RABV).…”
Section: Introductionmentioning
confidence: 99%
“…En Europe, de rares cas de transmission de virus EBLV-1 ont été observés chez des mammifères non volants, sans aboutir à un nouveau cycle épidémiologique. Les deux seuls cas rapportés en France concernaient des chats, dont l'un est décédé de la rage en Vendée en 2007 [3].…”
Section: Revuesunclassified
“…Le risque de transmission de ces espèces européennes à l'homme est très faible puisque seuls cinq cas humains (dont deux non confirmés biologiquement) leur ont été attribués depuis les années 1950 [3]. En revanche, la rage desmodine (transmise par des chauves-souris hématophages, Desmondus rotondus) est devenue la principale source de rage humaine dans certains pays d'Amérique.…”
unclassified
“…Some of the sporadic cases of human rabies have been reported from EBLV-1 and EBLV-2 (Kuzmin & Rupprecht, 2007;Kuzmin et al, 2011). However, in terrestrial mammals some of the sporadic cases of EBLV-1 infection were also reported which might be a potential source for human exposure (Dacheux et al, 2009). In France, neutralizing antibodies against EBLV-1 were detected in six species (Pipistrellus pipistrellus, P. kuhlii, Hypsugo savii, Plecotus austriacus, Eptesicus serotinus and Tadarida teniotis) of bats (López-Roig et al, 2014).…”
Section: Other Lyssavirusesmentioning
confidence: 99%